Negative ion relaxation and reactions in a cryogenic storage ring. Issue 6 (January 2020) - Schmidt, H T; Rosén, S; Thomas, R D; Stockett, M H; Geppert, W D; Larson, Å; Löfgren, P; Simonsson, A; Källberg, A; Reinhed, P; Björkhage, M; Blom, M; et al.
Abstract: An overview of recent experimental results of studies of negative atomic and molecular ions in the Double ElectroStatic Ion-Ring ExpEriment, DESIREE is given. Metastable level lifetimes in atomic negative ions have been measured by time-dependent laser photodetachment. Rotational relaxation of diatomic anions is studied by near-threshold photodetachment. Spontaneous decays of small metal cluster anions by electron emission and fragmentation is studied with decay-channel specificity. Finally, mutual neutralisation of pairs of negative and positive ions has been investigated with initial and final state selectivity.